Granulated blast furnace slag powder (GGBFS)-based tile adhesive
By adding a specific proportion of calcium sulfate, OPC and anhydrous calcium sulfaaluminate to the cement based on GGBS, and using appropriate polymers and rheology modifiers, the carbonization problem of cement in the presence of carbon dioxide and the irritation problem of alkaline activators is solved, and the effect of improving the mechanical properties and durability of the mortar is achieved.
Patent Information
- Application Number
- CN202380057780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-25
- Publication Date
- 2025-05-02
AI Technical Summary
Existing GGBS-based cements are rapidly carbonized in the presence of carbon dioxide, resulting in a decrease in flexural strength. At the same time, alkaline activators are irritating to users, and traditional polymers are intolerant in alkaline environments.
A hydraulic cementitious material composition containing granulated blast furnace slag powder (GGBS), more than 5% calcium sulfate, a small amount of ordinary silicate cement (OPC) and anhydrous calcium sulfaaluminate, is used, and complex and thickening polymers such as carboxymethyl cellulose (CMC) or gum arabic (GA) are added, as well as rheology modifiers such as cellulose ether.
It improves the mechanical properties and durability of the mortar, reduces the use of alkaline activators, reduces carbon dioxide emissions, and maintains stable performance in an alkaline environment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] The present disclosure relates to the field of hydraulic cementitious materials compositions containing granulated blast furnace slag powder (GGBS or slag) for preparing industrial mortars. In particular, the technical field of the present invention relates to hydraulic inorganic cementitious materials containing granulated blast furnace slag powder, which are used for compositions capable of setting and hardening, such as mortar compositions.
[0002] The invention also relates to the preparation method of these hydraulic cementitious material compositions and such mortar compositions capable of setting and hardening. Background Art
[0003] The production of Portland cement has a strong and negative impact on the environment due to the emission of large amounts of carbon dioxide. In the production of cement, CO2 is inevitably generated by decarbonation of limestone during the calcination of raw materials in the kiln at very high temperatures (1450°C) (Equation (1)):
[0004]
[0005] In addition, the combustion of fossil fuels needed to heat cement kilns releases CO2. Together with additional emissions from grinding, each ton of Portland cement produces almost one ton of CO2. Overall, the cement industry accounts for around 7% to 9% of global CO2 emissions.
[0006] Furthermore, handling of Portland cement may lead to health problems (e.g. allergies), especially due to its high alkalinity (pH above 13). Furthermore, harmful elements such as hexavalent chromium (Cr(VI)) may be released during kneading, which is also unhealthy for workers when in contact with the skin. Although Cr(VI) reducing agents (e.g. ferrous sulfate) are often included in cement powders, their effectiveness is limited by time. Construction workers, especially those in the third world, are not expected to frequently check the deadlines associated with these treatments.
[0007] Most current research into new cementitious materials aims to replace cement in various applications with cementitious materials that have less impact on the environment. One approach is by using resources that do not require expensive disposal, such as by-products from other industries (waste for one industry, but a major resource for others). This is the case with blast furnace slag, a by-product of the steel industry. By grinding this product into a fine powder (GGBS), a cementitious material can be obtained that can be used as a partial replacement for cement or alone, by adding some chemical activators.
[0008] It is noteworthy that the use of GGBS is not only environmentally friendly, but also leads to the enhancement of several properties when used for formulating mortars, such as high resistance to sulfate attack, low permeability, good resistance in chemically aggressive environments, low heat of hydration (required in large structures), overall excellent durability, possibility of fixing heavy metals or radionuclides, etc.
[0009] However, in contrast to Portland cement, cements based on GGBS require alkaline activators to form hardened mortars. Unfortunately, these alkaline activators are irritating to the user. Some efforts have been made to limit the amount of alkaline activators required. For example, patent US 8,932,402 B2 discloses hydraulic cementitious material compositions in which the amount of alkaline activator (base) is 1% by weight or less. Although this reduced amount of alkaline activator is beneficial, the mechanical properties of the resulting mortar can also be improved.
[0010] Typically, calcium sulfate is used to accelerate the hardening of GGBS-based cements. However, supersulfated cements with high GGBS content and more than 5 wt% calcium sulfate will carbonize rapidly in the presence of carbon dioxide, even at atmospheric concentrations, which results in a decrease in flexural strength.
[0011] Organic polymers, such as cellulose ethers, latex, retarders, water reducers and anti-shrinkage agents, are often used to adjust the rheological state of mortar and improve the long-term mechanical and durability properties.
[0012] Some organic polymers, such as cellulose ethers and latex, are essential ingredients of some industrial mortars, such as tile adhesives, repair agents, etc. Unfortunately, in GGBS-rich based cementitious material compositions with alkali activation system / rich cation activation system, most polymers, such as cellulose ethers and latex, are not resistant to alkaline environment / cationic environment, and their effects are strongly affected.
[0013] In this context, the present invention aims to solve at least one of the above problems and / or needs by achieving at least one of the following objectives:
[0014] -01- Provided is a GGBS-based cementitious material or a mortar composition comprising the GGBS-based cementitious material, which is an attractive alternative to ordinary Portland cement (OPC)-based compositions.
[0015] -O2- Provided is a slag-based cementitious material or a mortar composition including the GGBS-based cementitious material, which is environmentally friendly.
[0016] -03- To provide a slag-based cementitious material or a mortar composition comprising the GGBS-based cementitious material, which is more acceptable than an OPC-based composition in terms of health and safety issues.
[0017] -04- Provided is a slag-based cementitious material or a mortar composition comprising the GGBS-based cementitious material, which can produce dry mortar preparations and wet mortar preparations with suitable capabilities, which can be prepared by several methods such as vibration compaction, spraying, troweling, casting, etc.
[0018] -05- Provide a slag-based cementitious material or a mortar composition comprising the GGBS-based cementitious material, which can produce a wet preparation with suitable rheological properties, i.e., stable rheological properties (good workability) within a typical setting time (e.g., several minutes to several hours) required by the user of the wet preparation.
[0019] -06- Provided is a slag-based cementitious material or a mortar composition comprising the GGBS-based cementitious material, which can produce a hardened material having desired mechanical properties, in particular acceptable early strength (eg at 24 hours).
[0020] -07- Provided is a slag-based cementitious material or a mortar composition including the GGBS-based cementitious material, which can produce a hardened material having desired durability.
[0021] -08- Provided is a slag-based cementitious material or a mortar composition including the GGBS-based cementitious material, which can produce a hardened material with a generally desired setting time (eg, several minutes to several hours).
[0022] -O9- Provided is a simple and inexpensive method for preparing a GGBS-based cementitious material or a mortar composition comprising the GGBS-based cementitious material that meets at least one of objectives -O1- to -O8-.
[0023] -010- A simple and inexpensive method for preparing a slag-based cementitious material or a mortar composition comprising the GGBS-based cementitious material in a wet form is provided.
[0024] -O11- A hardening product comprising GGBS as a main component of a hydraulic binder is provided for use in the construction industry.
[0025] -O12- Strength enhancing admixtures are proposed to improve the hydration of sulfated cement. Summary of the invention
[0026] The above objects are achieved thanks to a tile adhesive composition comprising at least one aggregate and a hydraulic binder formulation comprising:
[0027] ·Ground granulated blast furnace slag (GGBS),
[0028] more than 5% by weight and preferably up to 30% by weight of calcium sulfate,
[0029] 5% by weight or less of ordinary Portland cement (OPC),
[0030] 10% by weight or less of cement containing anhydrous calcium sulphoaluminate (ye'elimite), clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0031] at least one complexing and thickening polymer selected from carboxymethylcellulose (CMC), gum arabic (GA), guar gum, guar ether, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymer (SAP), and
[0032] - At least one rheology modifier different from the complexing and thickening polymer, such as a cellulose ether.
[0033] The present invention also relates to a dry mortar composition comprising the brick and tile adhesive composition.
[0034] The present invention also relates to a wet mortar composition comprising the brick and tile adhesive composition.
[0035] The present invention also relates to a hardened mortar obtained from the above wet mortar composition.
[0036] Furthermore, the present invention also relates to a method for preparing the above-mentioned wet mortar composition, which comprises the step of mixing water with the above-mentioned brick and tile adhesive composition, wherein the brick and tile adhesive composition is prepared in situ from at least some of the different components of the brick and tile adhesive composition separately before or during the mixing step and / or in the form of one or more premixes.
[0037] The present invention also relates to a method for improving the hydration of sulfated cement comprising:
[0038] ·Ground granulated blast furnace slag (GGBS),
[0039] more than 5% by weight and preferably up to 30% by weight of calcium sulfate,
[0040] 5% by weight or less of ordinary Portland cement (OPC),
[0041] 10 wt. % or less of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0042] The method comprises the following steps:
[0043] S1: Provide the following components:
[0044] ·Ground granulated blast furnace slag (GGBS),
[0045] Calcium sulfate,
[0046] Ordinary Portland Cement (OPC),
[0047] cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0048] S2: providing at least one strength enhancing admixture which is a complexing and thickening polymer selected from carboxymethyl cellulose (CMC), gum arabic (GA), guar gum, guar gum ethers, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymer (SAP), preferably selected from CMC and GA, and
[0049] S3: Providing at least one rheology modifier other than the complexing and thickening polymer, such as a cellulose ether
[0050] S4: Mix the components with water.
[0051] definition
[0052] For the purposes of this document, the following non-limiting definitions must be considered:
[0053] "Slag" means the stony by-product material separated from the metal during the smelting or refining of the ore.
[0054] “GGBS” or “GGBFS”: Ground granulated blast furnace slag, which is equivalent to blast furnace slag, granulated blast furnace slag (GBFS), crushed blast furnace slag powder and blast furnace slag fines.
[0055] "Clinker" and "cement" are understood to mean powdered substances produced for use in making mortar. They are inorganic cementitious materials and may not contain any organic compounds.
[0056] "Cementitious material" means "hydraulic cementitious material", which refers to any material that hardens simply by adding water, such as GGBS and cement.
[0057] "Mortar" refers to a material composed of one or more cementitious materials, aggregates such as sand, and other components such as admixtures.
[0058] "d 50 "gives the median size of the particle size distribution of the material particles (usually in micrometers in cementitious materials). It means that 50% by weight of the particles have a size smaller than the specified number and 50% by weight of the particles have a size larger than the given number. 50 The measurement is performed by laser diffraction analysis using a wet method by means of a laser diffraction analyzer such as the "Mastersizer 2000" and commercialized by the company MALVERN, also known as laser diffraction spectroscopy.
[0059] "Water retainers" are compounds that have the property of remaining mixed with water before setting. They trap water in the wet preparation paste, thus improving its cohesiveness. To the extent that less water is absorbed by the substrate.
[0060] "Thickener" refers to a compound that increases the viscosity of a composition.
[0061] "X or less than X" without any indicated lower limit means that "X" and "0" are included in the range.
[0062] “A to B” means that A and B are included in the range. DETAILED DESCRIPTION
[0063] As described above, the present invention relates to a tile adhesive composition comprising at least one aggregate and a hydraulic binder formulation, wherein the hydraulic binder formulation comprises:
[0064] ·Ground granulated blast furnace slag (GGBS),
[0065] more than 5% by weight and preferably up to 30% by weight of calcium sulfate,
[0066] 5 wt% or less of ordinary Portland cement (OPC),
[0067] 10 wt. % or less of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0068] at least one complexing and thickening polymer selected from carboxymethylcellulose (CMC), gum arabic (GA), guar gum, guar ethers, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymers (SAP), and
[0069] - At least one rheology modifier different from the complexing and thickening polymer, such as a cellulose ether.
[0070] Granulated blast furnace slag (GGBS)
[0071] In some embodiments, the amount of GGBS is from 55 wt% to 95 wt%, advantageously from 65 wt% to 95 wt%, and more advantageously from 75 wt% to 95 wt%.
[0072] In an advantageous embodiment, at least part of the GGBS is ultrafine GGBS. Ultrafine GGBS is a material having a particle size of 6000 g / cm 2 Up to 8500g / cm 2 , advantageously 6500 g / cm 2 Up to 8250g / cm 2 , and more advantageously 7000 g / cm 2 Up to 8000g / cm 2 D 50 In this advantageous embodiment, the hydraulic binder composition according to the invention comprises GGBS, wherein 1 wt. % to 50 wt. %, advantageously 5 wt. % to 35 wt. %, and more advantageously 12 wt. % to 24 wt. % of the GGBS is ultrafine GGBS.
[0073] This proportion of ultrafine GGBS leads to an improvement in the water resistance of the resulting hardened mortar compared to a mortar according to the invention which does not contain ultrafine GGBS.
[0074] Calcium sulfate
[0075] The hydraulic binder composition according to the invention comprises more than 5% by weight and preferably at most 30% by weight of calcium sulfate.
[0076] Calcium sulfate can be anhydrite calcium sulfate, hemihydrate calcium sulfate, dihydrate calcium sulfate or a mixture thereof. Advantageously, the amount of calcium sulfate is 5% to 30% by weight, advantageously 5% to 25% by weight, and more advantageously 5% to 20% by weight.
[0077] Ordinary Portland Cement (OPC)
[0078] According to the present invention, the hydraulic binder may contain 5 wt % or less, advantageously 0 wt % to 2.5 wt % or less, and more advantageously 0 wt % to 0.5 wt % or less of OPC.
[0079] In this disclosure, OPC refers to any OPC that complies with standard EN 197-1.
[0080] Cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC) and calcium aluminate clinker
[0081] Advantageously, in the hydraulic binder composition, the total amount of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate and CAC is 0 wt % to 10 wt %, advantageously 0.5 wt % to 5 wt %, and more advantageously 2.5 wt % to 5 wt %.
[0082] The presence of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate and / or CAC can improve the early strength of the resulting hardened mortar at 24 h.
[0083] The cement containing anhydrous calcium sulphoaluminate may be sulphoaluminate cement (CSA).
[0084] In an advantageous embodiment, the hydraulic binder composition comprises 10 to 80 wt % CSA, advantageously 30 to 70 wt % CSA, and more advantageously 40 to 60 wt % CSA.
[0085] CAC can be selected from calcium aluminate (CA) and / or mayenite (C 12 A7) group.
[0086] Complexing and thickening polymers
[0087] According to the present invention, the hydraulic binder composition comprises at least one complexing and thickening polymer selected from carboxymethylcellulose (CMC), gum arabic (GA), guar gum, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum. In a preferred embodiment, the complexing and thickening polymer is selected from the group consisting of CMC and GA.
[0088] Advantageously, the amount of organic complexing and thickening agent is from 0% to 1.0% by weight, advantageously from 0.1% to 0.5% by weight and more advantageously from 0.2% to 0.4% by weight.
[0089] Rheology Modifiers
[0090] The hydraulic binder composition according to the invention comprises at least one rheology modifier.
[0091] The rheology modifier may be selected from methylcellulose (MC), methylhydroxyethylcellulose (MHEC), methylhydroxypropylcellulose (MHPC), hydroxyethylcellulose (HEC) and hydroxypropylcellulose (HPC), ethylhydroxyethylcellulose (EHEC).
[0092] In advantageous embodiments, the amount of rheology modifier is from 0 wt % to 1.0 wt %, advantageously from 0.1 wt % to 0.5 wt %, and more advantageously from 0.2 wt % to 0.4 wt %.
[0093] aggregate
[0094] Aggregates comprise a broad class of granular materials used in construction, including sand, gravel, crushed stone, slag (ungranulated), recycled concrete, and geosynthetic aggregates. They act as reinforcements to increase the strength of the overall composite.
[0095] Dry mortar composition
[0096] The present invention also relates to a dry mortar composition comprising the above-mentioned brick and tile adhesive and composition. The dry mortar composition may finally contain other admixtures and other additives.
[0097] According to the present invention, a "dry" mortar composition refers to a composition that is in powder form and is ready to be mixed with water. In other words, the dry mortar composition of the present invention may contain some moisture, but it essentially contains solid components intended to be mixed with water before application.
[0098] Advantageously, the dry mortar composition may comprise, in addition to the aggregate, one or more ingredients, in particular functional admixtures, additives and fibers. In particular, these ingredients are selected from the group of additives selected from fillers, auxiliary cementitious materials, water-reducing polymers, latex, water-retaining agents, rheological agents, defoamers / antifoaming agents, biocides, pigments, flame retardants, air entraining agents and retarders including, for example, the following compounds:
[0099] Defoamer / antifoaming agent
[0100] Possible defoamers are preferably selected from the group comprising, more preferably consisting of, polyhydroxy polyethers and mixtures thereof.
[0101] Biocides
[0102] Possible biocides are preferably selected from the group comprising, more preferably consisting of, inorganic oxides such as zinc oxide and mixtures thereof.
[0103] ·pigment
[0104] Possible pigments are preferably selected from the group comprising, more preferably consisting of, TiO2, iron oxides and mixtures thereof.
[0105] Flame retardant
[0106] Flame retardants (or fireproofing agents) can increase the fire resistance of a composition and / or reduce the rate at which flames spread from the composition.
[0107] Air entraining agent
[0108] The air entraining agent (surfactant) is advantageously selected from the group comprising, more preferably consisting of, natural resins, sulfated or sulfonated compounds, synthetic detergents, organic fatty acids and mixtures thereof, preferably from the group comprising, more preferably consisting of, lignin sulfonates, alkaline soaps of fatty acids and mixtures thereof, and more preferably from the group comprising, more preferably consisting of, olefin sulfonates, sodium lauryl sulfate and mixtures thereof.
[0109] Retarder
[0110] The retarder is advantageously selected from the group comprising, more preferably consisting of: tartric acid and its salts: sodium or potassium; citric acid and its salts: sodium (trisodic citrate) and mixtures thereof.
[0111] In addition, other components may be:
[0112] Plasticizer
[0113] ·fiber
[0114] ·Dispersion powder
[0115] Wetting agent
[0116] Polymer resin
[0117] Complexing agent
[0118] · Drying shrinkage reducing agents based on polyols.
[0119] The total content of these optional other components included in the dry mortar composition is preferably 0% to 5% by weight of the total weight of the cementitious material composition. 5% by weight , advantageously from 0.2% to 2% by weight, and more advantageously from 0.5% to 1% by weight.
[0120] Wet mortar composition
[0121] The present invention also relates to a wet mortar composition comprising the brick and tile adhesive composition and water.
[0122] In a specific embodiment, in the wet mortar composition according to the present invention, the mass ratio of water / hydraulic binder composition is from 0.30 to 0.63, advantageously from 0.34 to 0.48, and more advantageously from 0.38 to 0.42.
[0123] Method for preparing a wet mortar composition
[0124] The invention also relates to a method for preparing the above-mentioned wet mortar composition, which comprises a step of mixing water with at least the above-mentioned tile adhesive composition, the tile adhesive composition being prepared in situ from at least some of the different components of the cementitious material composition separately before or during the mixing step and / or in the form of one or more than one premix.
[0125] In other words, the wet mortar composition can be prepared by two different methods.
[0126] In the first method, a tile adhesive composition is prepared. Thereafter, a dry mortar composition is mixed with water.
[0127] In the second method, a wet mortar composition is prepared by mixing the components of the tile adhesive composition in water.
[0128] According to the present disclosure, the term "mixing" has to be understood as any form of mixing.
[0129] In a preferred embodiment, a portion of the cementitious composition is mixed with at least a portion of the water prior to mixing with the aggregate.
[0130] Hardened industrial mortar composition
[0131] The present invention also relates to a hardened mortar composition obtained from the above wet mortar composition.
[0132] Method for improving the hydration of sulfated cement
[0133] As stated above, the present invention also relates to a method for improving the hydration of sulfated cement comprising:
[0134] ·Ground granulated blast furnace slag (GGBS),
[0135] more than 5% by weight and preferably up to 30% by weight of calcium sulfate,
[0136] 5% by weight or less of ordinary Portland cement (OPC),
[0137] 10 wt. % or less of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0138] The method comprises the following steps:
[0139] S1: Provide the following components:
[0140] ·Ground granulated blast furnace slag (GGBS),
[0141] Calcium sulfate,
[0142] Ordinary Portland Cement (OPC),
[0143] cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof,
[0144] S2: providing at least one strength enhancing admixture which is a complexing and thickening polymer selected from carboxymethyl cellulose (CMC), gum arabic (GA), guar gum, guar gum ethers, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymer (SAP), preferably selected from CMC and GA, and
[0145] S3: providing at least one rheology modifier different from the complexing and thickening polymer, such as a cellulose ether,
[0146] S4: Mix the components with water.
[0147] The components provided in step S1, step S2 and step S3 may be mixed before the mixing step S4 or mixed in situ during the mixing step, and the components may be used individually and / or in the form of one or more than one premix.
[0148] In other words, the method can be implemented in two different ways.
[0149] In the first method, the components provided in step S1, step S2 and step S3 are mixed together and thereafter mixed with water in step S4.
[0150] In the second method, the components provided in step S1, step S2 and step S3 are introduced into water one by one, or some of the components are introduced into water in the form of a premix, and then the mixing step S4 is performed.
[0151] Example
[0152] Example 1: A brick and tile adhesive composition comprising a hydraulic cementitious material according to the present invention
[0153] The hydraulic cementitious material composition was prepared by mixing the following materials: GGBS, calcium sulfate, OPC, a 5000 ± 250 cm 2 / g of Blaine and containing more than 55% of anhydrous calcium sulfoaluminate and less than 10% of belitte CSA, cellulose ether UP1560 sold by Ashland® and CMC, the proportions of which are shown in Table 1 below, together accounting for 47.48% of the dry mixture.
[0154]
[0155] Table 1
[0156] This hydraulic binder composition was mixed with 2.5% by weight of latex Vinnapas 7220 sold by Wacker® and 50.02% by weight of sand to obtain a dry tile adhesive composition according to the invention.
[0157] Thereafter, the dry tile adhesive composition was mixed with 19 wt % of water relative to the total weight of the dry tile adhesive composition to obtain a wet tile adhesive composition according to the present invention.
[0158] The initial consistency of the wet tile adhesive composition according to the present invention is 431 Pa*s. The adhesive strength of the hardened tile adhesive is in accordance with standard EN12004 and is of type C2TE, as shown in Table 2 below, where measurements of three samples of the hardened tile adhesive composition were performed at 24 hours, 7 days, 14 days and 28 days to study the strength evolution when stored at (20±2)°C and (50±5)% relative humidity.
[0159]
[0160] Table 2 Adhesive strength (unit: MPa equal to N / mm 2 )
[0161] Opening hours 20分钟 and opening hours 30分钟 It is defined as “the maximum interval after application of a tile adhesive at which the tile can be embedded in the applied adhesive and meet the specified tensile bond strength requirements”. To evaluate the open time, after preparation of the test unit, the tile is measured from T 0分钟 Initially, five tiles were placed on the fresh adhesive after 20 minutes and 30 minutes respectively, and loaded with a weight of 20 N for 30 seconds.
[0162] After drying for 7 days under dry conditions at (20 ± 2) ° C and (50 ± 5)% relative humidity, the test unit is immersed in water at standard temperature. After 20 days, the test unit is removed from the water and wiped with a cloth, and the pull-head plate is glued to the tile. After another 24 hours, which is necessary for the drying of the adhesive, the test unit is immersed in water. On the 28th day, the test unit is removed from the water and immediately pulled off with a tensile tester for WATER measurement.
[0163] After drying for 14 days at (20±2)°C and (55±5)% relative humidity, the test units were placed in an air-circulating oven at (70±3)°C for another 14 days. Subsequently, they were removed from the oven, the slider plate was glued to the tile, and left for another 24 hours under standard conditions, which is necessary to dry the adhesive. At the 28th day, the test units were pulled off using a tensile tester for the HEAT measurement.
[0164] Embodiment 2:
[0165] The hydraulic cementitious material composition was prepared by mixing the following materials: GGBS, calcium sulfate, OPC, a 5000 ± 250 cm 2 / g of Blaine and containing more than 55% of anhydrous calcium sulfoaluminate and less than 10% of Belite CSA, cellulose ether UP1560 sold by Ashland® and GA, the proportions of which are shown in Table 3 below:
[0166]
[0167] Table 3
[0168] This hydraulic binder composition was mixed with 2.5% by weight of latex Vinnapas 7220 sold by Wacker® and 50.02% by weight of sand to obtain a dry tile adhesive composition according to the invention.
[0169] Thereafter, the dry tile adhesive composition was mixed with 19 wt % of water relative to the total weight of the dry tile adhesive composition to obtain a wet tile adhesive composition according to the present invention.
[0170] The initial consistency of the wet tile adhesive composition according to the present invention is 367 Pa*s. The adhesive strength of the hardened tile adhesive is in accordance with standard EN12004 and is of type C2TE, as shown in Table 4 below, where measurements of three samples of the hardened tile adhesive composition were performed at 24 hours, 7 days, 14 days and 28 days to study the strength evolution when stored at (20±2)°C and (50±5)% relative humidity.
[0171]
[0172] Table 4 Adhesive strength (unit: MPa equal to N / mm 2 )
Claims
1. A tile adhesive composition comprising at least one aggregate and a hydraulic binder formulation, wherein the hydraulic binder formulation comprises: ·Ground granulated blast furnace slag (GGBS), more than 5% by weight and preferably up to 30% by weight of calcium sulfate, 5 wt% or less of ordinary Portland cement (OPC), 10 wt. % or less of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof, at least one complexing and thickening polymer selected from carboxymethylcellulose (CMC), gum arabic (GA), guar gum, guar ethers, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymers (SAP), preferably selected from CMC and GA, and - At least one rheology modifier different from the complexing and thickening polymer, such as a cellulose ether.
2. The tile adhesive composition according to claim 1, wherein the complexing and thickening polymer is selected from CMC and GA.
3. The tile adhesive composition according to any one of the preceding claims, wherein the amount of GGBS is 55 to 95 wt %, advantageously 65 to 95 wt %, and more advantageously 75 to 95 wt %.
4. The tile adhesive composition according to any one of the preceding claims, wherein the amount of calcium sulfate is more than 5% to 30% by weight, advantageously more than 5% to 25% by weight, and more advantageously more than 5% to 20% by weight.
5. A tile adhesive composition according to any one of the preceding claims, wherein the amount of OPC is less than 3 wt%, more advantageously less than 2 wt% and even more advantageously less than 1 wt%.
6. The tile adhesive composition according to claim 5, wherein the total amount of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate and / or CAC is 0 wt % to 10 wt %, advantageously 0.5 wt % to 5 wt %, and more advantageously 2.5 wt % to 5 wt %.
7. The tile adhesive composition according to any one of the preceding claims, wherein the amount of organic complexing and thickening agent is from 0% to 1.0% by weight, advantageously from 0.1% to 0.5% by weight, and more advantageously from 0.2% to 0.4% by weight.
8. The tile adhesive composition according to any one of the preceding claims, wherein the amount of rheology modifier is from 0 wt% to 1.0 wt%, advantageously from 0.1 wt% to 0.5 wt%, and more advantageously from 0.2 wt% to 0.4 wt%.
9. The tile adhesive composition according to any one of the preceding claims, wherein 1 wt% to 50 wt%, advantageously 5 wt% to 35 wt%, and more advantageously 12 wt% to 24 wt% of the GGBS is ultrafine GGBS.
10. A dry mortar composition comprising the tile adhesive composition according to any one of claims 1 to 89.
11. The dry mortar composition according to claim 10, wherein it further comprises at least one additive selected from the group consisting of fillers, auxiliary cementitious materials, water reducing polymers, latex, water retaining agents, rheological agents, defoamers / antifoaming agents, biocides, pigments, flame retardants, air entraining agents and retarders.
12. A wet mortar composition comprising the tile adhesive composition according to any one of claims 1 to 9 and water.
13. The wet mortar composition according to claim 12, wherein the mass ratio of water / cementitious material composition is from 0.30 to 0.63, advantageously from 0.34 to 0.48, and more advantageously from 0.38 to 0.
42.
14. A hardened mortar obtained from the wet mortar composition according to any one of claims 12 and 13.
15. A method for preparing a wet mortar composition according to any one of claims 12 and 13, comprising the step of mixing water with at least one aggregate according to any one of claims 1 to 9 and a hydraulic binder composition, the cementitious composition being prepared in situ from at least some of the different components of the cementitious composition separately and / or in the form of one or more than one premix before or during the mixing step.
16. A method for improving the hydration of sulfated cement, the sulfated cement comprising: ·Ground granulated blast furnace slag (GGBS), more than 5% by weight and preferably up to 30% by weight of calcium sulfate, 5 wt% or less of ordinary Portland cement (OPC), 10 wt. % or less of cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof, The method comprises the following steps: S1: Provide the following components: ·Ground granulated blast furnace slag (GGBS), Calcium sulfate, Ordinary Portland Cement (OPC), cement containing anhydrous calcium sulphoaluminate, clinker containing anhydrous calcium sulphoaluminate, calcium aluminate cement (CAC), calcium aluminate clinker or mixtures thereof, S2: providing at least one strength enhancing admixture which is a complexing and thickening polymer selected from carboxymethylcellulose (CMC), gum arabic (GA), guar gum, guar gum ethers, agar, carrageenan, xanthan gum, chitosan, pectin, hyaluronic acid, locust bean gum, super absorbent polymer (SAP), preferably selected from CMC and GA, and S3: providing at least one rheology modifier different from the complexing and thickening polymer, such as a cellulose ether, S4: Mix the components with water.
Citation Information
Patent Citations
Construction materials binders
US8932402B2